Difference between revisions of "De Morgan's Law"

From TRCCompSci - AQA Computer Science
Jump to: navigation, search
(Example 7)
(Video)
 
(12 intermediate revisions by 3 users not shown)
Line 3: Line 3:
  
 
[[File:capture3.jpg]]
 
[[File:capture3.jpg]]
 +
 +
Further explanation:
 +
 +
===Video===
 +
<youtube>https://www.youtube.com/watch?v=HoH0PrS3WNI&list=PLCiOXwirraUA9HyHoqOaGBU_k6nBRCb22&index=6</youtube>
 +
 +
https://www.youtube.com/watch?v=HoH0PrS3WNI&list=PLCiOXwirraUA9HyHoqOaGBU_k6nBRCb22&index=6
 +
 +
===TRC Video===
 +
<youtube>https://www.youtube.com/watch?v=O3w4yGY90SU</youtube>
 +
 +
https://www.youtube.com/watch?v=O3w4yGY90SU
  
 
==The Process==
 
==The Process==
Line 9: Line 21:
 
===Step 2 - Negate each term===
 
===Step 2 - Negate each term===
 
===Step 3 - Negate the whole expression===
 
===Step 3 - Negate the whole expression===
 +
 +
It is recommended to "Break the longest line" when applying De Morgan's law.
 +
 +
You can often treat a whole set of brackets as a single term.
  
 
==How to apply==
 
==How to apply==
 
===Example 1===
 
===Example 1===
 +
  
 
<math> \overline{(\overline{A+B})+B} </math>
 
<math> \overline{(\overline{A+B})+B} </math>
 +
 +
Now we use De Morgan's law to the whole equation and we treat A+B as one.
 +
 +
<math> (A+B).\overline {B} </math>
 +
 +
<math> \overline {B}.A + (\overline{B}.B) </math>
 +
 +
<math> \overline{B}.A + 0 </math>
 +
 +
<math> \overline{B}.A </math>
  
 
===Example 2===
 
===Example 2===
Line 19: Line 46:
  
 
===Example 3===
 
===Example 3===
<math> \overline{((\overline{A+B}).\overline{A}} </math>
+
<math> \overline{(\overline{A+B}).\overline{A}} </math>
  
 
Simplifying by using De Morgan's Law:
 
Simplifying by using De Morgan's Law:
Line 25: Line 52:
 
1. Swap the sign:
 
1. Swap the sign:
  
<math> \overline{((\overline{A.B})+\overline{A}} </math>
+
<math> \overline{(\overline{A+B})+\overline{A}} </math>
  
2. Negate each expression:
+
2. Negate each term:
  
<math> \overline{((A.B)+A} </math>
+
<math> \overline{\overline{\overline{(A+B)}}+\overline{\overline{A}}} </math>
  
 
3. Negate the whole Expression:
 
3. Negate the whole Expression:
  
<math>((A.B)+A </math>
+
<math> \overline{\overline{\overline{\overline{(A+B)}}+\overline{\overline{A}}}} </math>
 +
 
 +
Or:
 +
 
 +
<math>(A+B)+A </math>
  
 
Using Redundancy law this expression can be simplified to:
 
Using Redundancy law this expression can be simplified to:
Line 42: Line 73:
  
 
===Example 4===
 
===Example 4===
<math> (\overline{A} + B) . \overline{(A + (\overline{B +A})}) </math>
+
<math> (\overline{A} + B) . \overline{(A + (\overline{B + A})}) </math>
 +
 
 +
Applying De Morgan's law to the inner bracket
 +
 
 +
<math> (\overline{A} + B) . \overline{(A + (B + A)}) </math> Inverting the not gate above the bracket
 +
 
 +
<math> (\overline{A} + B) . \overline{(A + (B . A)}) </math> Swapping signs
 +
 
 +
<math> (\overline{A} + B) . \overline{(A + (\overline{B} . \overline{A})}) </math> Inverting not gates above terms
 +
 
 +
Applying De Morgan's law to the right bracket
 +
 
 +
<math> (\overline{A} + B) . (A + (\overline{B} . \overline{A})) </math> Inverting the top not gate
 +
 
 +
<math> (\overline{A} + B) . (A . (\overline{B} + \overline{A})) </math> Swapping signs
 +
 
 +
<math> (\overline{A} + B) . (\overline{A} . (B + A)) </math> Inverting not gates above terms
 +
 
 +
Now that it is easier to simplify, we can do that
 +
 
 +
<math> (\overline{A} + B) . ((\overline{A} . B) + (\overline{A} . A))) </math> Applying the distributive law
 +
 
 +
<math> (\overline{A} + B) . ((\overline{A} . B) + 0)) </math> Applying an identity law
 +
 
 +
<math> (\overline{A} + B) . (\overline{A} . B) </math>
 +
 
 +
<math> (\overline{A} . \overline{A} . B) + (B . \overline{A} . B) </math> Expand the brackets
 +
 
 +
<math> (\overline{A} . B) + (\overline{A} . B) </math> Use identity <math> X . X = X </math>
 +
 
 +
<math> \overline{A} . B </math> Use identity <math> X + X = X </math>
  
 
===Example 5===
 
===Example 5===

Latest revision as of 09:05, 23 August 2023

DeMorgan's laws are the laws of how a NOT gate affects AND and OR statements. They can be easily remembered by "break the line, change the sign". The following image is how to prove De Morgan's Law...

Capture3.jpg

Further explanation:

Video

https://www.youtube.com/watch?v=HoH0PrS3WNI&list=PLCiOXwirraUA9HyHoqOaGBU_k6nBRCb22&index=6

TRC Video

https://www.youtube.com/watch?v=O3w4yGY90SU

The Process

Step 1 - Reverse the sign

Step 2 - Negate each term

Step 3 - Negate the whole expression

It is recommended to "Break the longest line" when applying De Morgan's law.

You can often treat a whole set of brackets as a single term.

How to apply

Example 1

[math] \overline{(\overline{A+B})+B} [/math]

Now we use De Morgan's law to the whole equation and we treat A+B as one.

[math] (A+B).\overline {B} [/math]

[math] \overline {B}.A + (\overline{B}.B) [/math]

[math] \overline{B}.A + 0 [/math]

[math] \overline{B}.A [/math]

Example 2

[math](\overline{A+\overline{B}).\overline{A}}[/math]

Example 3

[math] \overline{(\overline{A+B}).\overline{A}} [/math]

Simplifying by using De Morgan's Law:

1. Swap the sign:

[math] \overline{(\overline{A+B})+\overline{A}} [/math]

2. Negate each term:

[math] \overline{\overline{\overline{(A+B)}}+\overline{\overline{A}}} [/math]

3. Negate the whole Expression:

[math] \overline{\overline{\overline{\overline{(A+B)}}+\overline{\overline{A}}}} [/math]

Or:

[math](A+B)+A [/math]

Using Redundancy law this expression can be simplified to:

[math] A [/math]

This is because if A is 1, the output will always be 1, regardless of the value of B.

Example 4

[math] (\overline{A} + B) . \overline{(A + (\overline{B + A})}) [/math]

Applying De Morgan's law to the inner bracket

[math] (\overline{A} + B) . \overline{(A + (B + A)}) [/math] Inverting the not gate above the bracket

[math] (\overline{A} + B) . \overline{(A + (B . A)}) [/math] Swapping signs

[math] (\overline{A} + B) . \overline{(A + (\overline{B} . \overline{A})}) [/math] Inverting not gates above terms

Applying De Morgan's law to the right bracket

[math] (\overline{A} + B) . (A + (\overline{B} . \overline{A})) [/math] Inverting the top not gate

[math] (\overline{A} + B) . (A . (\overline{B} + \overline{A})) [/math] Swapping signs

[math] (\overline{A} + B) . (\overline{A} . (B + A)) [/math] Inverting not gates above terms

Now that it is easier to simplify, we can do that

[math] (\overline{A} + B) . ((\overline{A} . B) + (\overline{A} . A))) [/math] Applying the distributive law

[math] (\overline{A} + B) . ((\overline{A} . B) + 0)) [/math] Applying an identity law

[math] (\overline{A} + B) . (\overline{A} . B) [/math]

[math] (\overline{A} . \overline{A} . B) + (B . \overline{A} . B) [/math] Expand the brackets

[math] (\overline{A} . B) + (\overline{A} . B) [/math] Use identity [math] X . X = X [/math]

[math] \overline{A} . B [/math] Use identity [math] X + X = X [/math]

Example 5

[math] \overline{\overline{(\overline{A}+A.(A+B))} + (B . C)} [/math]

Example 6

[math] \overline{\overline{(A+A.(\overline{A+B}))} + (B . C)} [/math]

Example 7

[math] \overline{(\overline{A}+A.(A+B))} + \overline{(B.C)} [/math]

[math] \overline{(\overline{A}+A+A.B)}+(\overline{B}+\overline{C}) [/math]

[math] (A.\overline{A}.\overline{A}+\overline{B})+(\overline{B}+\overline{C}) [/math]

[math] (A.\overline{A}+\overline{B})+(\overline{B}+\overline{C}) [/math]

[math] (0+\overline{B})+(\overline{B}+\overline{C}) [/math]

[math] \overline {B}+(\overline{B}+\overline{C}) [/math]

[math] \overline{C}+(\overline{B}+\overline{B}) [/math]

[math] \overline{B}+\overline{C} [/math]